Adsorption of N, N-dimethylamine from aqueous solutions by a metal organic framework, MOF – 235. Issue 6 (3rd June 2019) - Beltrán-Suito, Rodrigo; Pinedo-Flores, Angela; Bravo-Hualpa, Fabiola; Ramos-Muñoz, Jorge; Sun-Kou, María del Rosario
Abstract: Water-resistant MOF-235 was used to adsorb N, N-dimethylamine (DMA) from aqueous solutions. It was synthesized from terephthalic acid and FeCl3 .6H2 O under air-free conditions and characterized by its crystalline structure, functional groups and temperature resistance. The kinetic data results were best adjusted to the pseudo-second order model (R 2 >0.963). The best-fit isotherm, Langmuir model, suggested the adsorption of DMA is localized on homogenously distributed active sites on the surface. This fit was confirmed by the value of β = 1 on the Redlich-Peterson model. Our study suggests that the manipulation of novel materials such as MOF-235 promises new avenues for water treatment solutions. Schematic structure of MOF-235 and its application as adsorbent. Graphical Abstract: